Faktor-Faktor Yang Mempengaruhi Penyerapan Anggaran Belanja Organisasi Perangkat Daerah Pemerintah Kota Palembang - Novita Dayang Sari; Maria Maria (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the factors that affect the absorption of the budget of the regional government organization of the Palembang city government. The population in this study were 51 OPD Palembang City Government. The data collection technique used a saturated sample with questionnaires distributed to 204 employees in 51 OPDs of the Palembang City Government with 4 respondents in each OPD. This study uses multiple linear regression analysis with SPSS version 25. Based on the results of the study it is known that Budget Planning has a positive and significant effect on Budget Absorption, Budget Execution has a positive and significant effect on Budget Absorption, Human Resource Competence has no effect on Budget Absorption, Procurement of Goods and Services has a positive and significant effect on Budget Absorption, and Organizational Commitment has no effect on Budget Absorption. Simultaneous testing shows that the variables of Budget Planning, Budget Execution, Human Resource Competence, Procurement of Goods and Services, and Organizational Commitment together affect Budget Absorption. The value of Adjusted R square is 0.793, which means Budget Planning, Budget Execution, Competence of Human Resources, Procurement of Goods and Services, and Organizational Commitment is 79% of Budget Absorption and the rest is influenced by other variables. Keywords: Budget Absorption, Budget Planning, Budget Execution, Human Resource Competence, Procurement of Goods and Services, Organizational Commitment